Tethered Aryl Groups Increase the Activity of Anti-Proliferative Thieno[2,3-b]Pyridines by Targeting a Lipophilic Region in the Active Site of PI-PLC - Natalie A. Haverkate; Euphemia Leung; Lisa I. Pilkington; David Barker (MDPI AG, 2021)
The compounds 2-amino-3-carboxamido-thieno[2,3-b]pyridines have demonstrated excellent anti-proliferative activity against human cancer cell lines, including the triple-negative breast cancer cell line MDA-MB-231. In this study, 81 novel thieno[2,3-b]pyridines were synthesised in four series to further improve their anti-proliferative activity, in particular by targeting an adjacent lipophilic pocket in the putative target enzyme phosphoinositide phospholipase C (PI-PLC). Overall, it was found that appending a propyl-aryl group at C-5 on 2-amino-3-carboxamido-thieno[2,3-b]pyridine resulted in compounds with potent biological activity, exhibiting IC50 values in the nanomolar range. The propyl linker could be an α,β-unsaturated ketone or a saturated propyl ketone, but the highest activity was obtained when allylic alcohols were the tether between thieno[2,3-b]pyridine and the appended aryl group, with compound 21r having IC50 values lower than 50 nM. Compounds with one extra carbon in the tether (i.e., a four-atom chain) were found to be considerably less active. Molecular modelling revealed this propyl tether places the newly introduced aryl ring in an untargeted lipophilic pocket within the active site of the phosphoinositide phospholipase C (PI-PLC) enzyme.